1983
DOI: 10.1515/cclm.1983.21.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 17β-Carboxyester Derivatives of Natural and Synthetic Glucocorticoids: Correlation Between Receptor Binding and Inhibition of in vitro Phytohaemagglutinin-Induced Lymphocyte Blastogenesis

Abstract: Summary: Several methyl 17ß-carboxyester derivatives of natural and fluorinated glucocorticoids were synthesized in order to compare their potency to compete for [ 3 H]dexamethasone binding sites in human spieen tumour cytosols (äs a source of large quantities of white blood cells) with their potency to inhibit phytohaemagglutinin-induced blastogenesis of normal human peripheral lymphocytes. The 17ß-carboxylic acids neither show binding activity nor Inhibition of blastogenesis. Methylation partially restores t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
2
9
0
1
Order By: Relevance
“…This hypothesis, however, assumes that the hormone binding sites of glucocorticoid receptors of different speaes are at least similar (21). On the contrary, we maintain, on the basis of the literature (16,17,22) and our own results (7), that a generalized rationale of structure-activity relationships for glucocorticoid hormones is at the moiiient impossible.…”
Section: Biscussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This hypothesis, however, assumes that the hormone binding sites of glucocorticoid receptors of different speaes are at least similar (21). On the contrary, we maintain, on the basis of the literature (16,17,22) and our own results (7), that a generalized rationale of structure-activity relationships for glucocorticoid hormones is at the moiiient impossible.…”
Section: Biscussionmentioning
confidence: 58%
“…The benzyl 17ß-carboxamide analogue of dexamethasone (compound Ic) behaved like a glucocorticoid agonist and the order of potency of this agonist was consistent with its affinity for human spieen tumour and rat liver receptors (4)(5)(6)(7).…”
mentioning
confidence: 69%
“…Rat liver and kidney cytosols from adrenalectomized feinale Wistar rats (150-200g) were prepared in the same way äs the uterine cytosol. For HPLC (high performance liquid chromatography) cytosol was prepared in ice-cold Tris/HCl-EDTA-buffer (20 ]RU 38486 together with a 200-ibld molar excess of unlabeled RÜ 38486 or R 5020 ünder identical incubation conditions. All incubations were carried out in triplicate.…”
Section: Preparation Of Tissue Samplesmentioning
confidence: 99%
“…This phenomenon is not general but tissue-specific. Carboxamide derivatives of dexamethasone, for example, are antiglucocorticoids in hepatoma cells (19), but are potent agonists in human peripheral lymphocytes (20).…”
Section: Time Studies Of [mentioning
confidence: 99%
“…Recent studies on corticosteroids for skin application has shown that the anti-inflammatory effects of mono-and di-ester derivatives of corticosteroids are more potent than the effects of free corticosteroids [1][2][3]. It is thought that corticosteroid esters having side chains of appropriate length tend to accumulate in skin and that the binding activity of the esters to the receptor is stronger than that of free corticosteroids [3,4].…”
Section: Introductionmentioning
confidence: 99%